Pengaruh CAR Dan FDR Terhadap Pembiayaan Murabahah Dengan NPF Sebagai Variabel Moderating - Yulyani, Evita; Diana, Nana (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to know the effect of CAR and FDR variables on Murabahah financing partially and simultaneously, besides, this study also examined the influence of NPF variables in moderating the relationship between independent variables and Murabahah financing. This research is a quantitative study with a sample of 11 (eleven) Syariah Commercial Banks registered with the Otoritas Jaa Keuangan in 2015-2019 that meet the researchers' criteria. The data used in this study is secondary data in the form of financial statements obtained from the website of each bank that is a sample of research. The results showed that CAR had no effect and significant on Murabahah financing, FDR had no effect and significant on Murabahah financing, and also simultaneously CAR and FDR did not affect muarabah financing. On the other side, the NPF as moderating variable show that a map to the CAR on Murabahah financing, the NPF moderating the FDR on Murabahah financing, and also the NPF moderating the influence of CAR and FDR on Murabahah financing simultaneously.